Determinants Of Innovative Work Behaviour Among Academics In Saudi Arabia: Quality Culture As Moderator - Harmal, Majed Ageel A (2024)
In recent years, there has been a notable increase in government financing and investment directed towards higher education institutions (heis) in saudi arabia. This trend highlights the crucial significance of academicians’ hard and soft skills in shaping their performance. The concept of academic innovative work behaviour (iwb) is strongly associated with the ability to come up with and share original ideas. The objective of this study is to further investigate the influence of academic talents on several aspects of innovative work behaviour, with a specific focus on the creation and advancement of novel ideas. Comprehending these processes is crucial for cultivating a culture of innovation within the academic domain. This study looks at the factors that influence innovative work behaviour (iwb) among academic staff in saudi arabian higher education institutions (heis). This study examines the impact of various factors on iwb, including extrinsic motivation, communication efficacy, selfdetermination, competence, management support, and psychological empowerment, with the moderating influence of quality culture, with a focus on the country’s underutilization of human resources for innovative ideas despite significant government investments in heis. Using an approach grounded in the selfdetermination theory and the social cognitive theory, the study analysed data from 390 assistant professors, associate professors, and professors.